2015
DOI: 10.1016/j.brat.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioural therapy for outpatients with eating disorders: Effectiveness for a transdiagnostic group in a routine clinical setting

Abstract: therapy for outpatients with eating disorders: Effectiveness for a transdiagnostic group in a routine clinical setting. Behaviour Research and Therapy,[68][69][70][71][72][73][74][75] https://doi.org/10.1016/j.brat.2015.03.001 eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
83
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(107 citation statements)
references
References 35 publications
19
83
0
1
Order By: Relevance
“…They do not have the range of professional backgrounds that are common in specialist eating disorders teams, but usually have training in appropriate therapies. For adult patients, this therapy base is commonly cognitive–behavioral therapy (CBT), given its proven benefits in clinical trials (Fairburn et al, ) and in routine practice in specialist eating disorder services (Byrne, Fursland, Allen & Watson, ; Knott, Woodward, Hoefkens & Limbert, ; Turner et al ). However, no studies to date have explored the effectiveness of CBT for eating disorders when delivered in a primary care setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They do not have the range of professional backgrounds that are common in specialist eating disorders teams, but usually have training in appropriate therapies. For adult patients, this therapy base is commonly cognitive–behavioral therapy (CBT), given its proven benefits in clinical trials (Fairburn et al, ) and in routine practice in specialist eating disorder services (Byrne, Fursland, Allen & Watson, ; Knott, Woodward, Hoefkens & Limbert, ; Turner et al ). However, no studies to date have explored the effectiveness of CBT for eating disorders when delivered in a primary care setting.…”
Section: Introductionmentioning
confidence: 99%
“…While recommendations for length of treatment for CBT for eating disorders vary from 15 to 40 sessions (depending on the version of CBT and the patient's BMI—Fairburn, ), there is provision within protocols for CBT to be extended if appropriate (Fairburn, 2008; Waller et al, ). However, effectiveness studies have also suggested that the therapy might be shortened in response to early changes, as well as allowing for extension (e.g., Turner et al, ). While it might be assumed that adding more sessions would have a stronger clinical effect, there is some indication that therapy effects are not linear with time.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in eating disorder research, a transdiagnostic model is being increasingly endorsed (Stice, Rohde, Butryn, Menke, & Marti, 2014;Turner, Marshall, Stopa, & Waller, 2015;Wade, Bergin, Martin, Gillespie, & Fairburn, 2006) as anorexia nervosa, bulimia nervosa and eating disorder not otherwise specified share the same core-pathology (Fairburn, Cooper, & Shafran, 2003) and distinctive clinical symptoms (Brockmeyer et al, 2013;Treasure, Claudino, & Zucker, 2010). Moreover, these disorders often move across from one to another in the course of time (Agras, Walsh, Fairburn, Wilson, & Kraemer, 2000;Castellini et al, 2011;Eddy, Dorer, Franko, Tahilani, Thompson-Brenner, & Herzog, 2008;Milos, Spindler, Schnyder, & Fairburn, 2005;Sullivan, Bulik, Fear, & Pickering, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Correlation with the BDI was r  = 0.85, with the BAI r  = 0.65 [24], with HADS anxiety r  = 0.74 and with HADS depression r  = 0.66 [25]. The CORE-OM has been widely and successfully used to measure emotional distress across a range of conditions such as chronic anxiety [26], depression [27], and eating disorders [28]. The items which make up the CORE-OM assess overall mental wellbeing by enquiring about both mental processes (e.g.…”
Section: Introductionmentioning
confidence: 99%